Alteplase: thrombolysis for acute ischemic stroke. Issue 5 (September 2005) - Kane, Ingrid; Sandercock, Peter
Alteplase is the only licensed thrombolytic agent for the treatment of acute ischemic stroke. The body of evidence to date suggests that it reduces the number of stroke patients who are dead or dependent at follow up, despite the risk of intracranial hemorrhage. However, in Europe, the license has only been granted for people aged under 80 years who fulfil specific criteria and who can be seen and treated within 3 h of symptom onset. There is a need for further data from randomized controlled trials to determine more precisely which patients are most likely to benefit and whether a wider variety of patients could be treated.